Observations of high burnup structure in AGR fuel. (November 2022) - Barker, Matthew A.; Adam, Martin S.; Little, Paul; Mills, Robert; Morgan, Susan; Woodman, Francesca E.
Abstract: Nuclear power plants (NPPs) within the UK are largely of the commercial advanced gas-cooled reactor (AGR) design. The key elements of the reactor and fuel design differ somewhat to those seen in Light Water Reactors (LWRs), most markedly the cladding, an austenitic stainless steel, and annular ceramic UO2 fuel pellets. The graphite moderated AGR cores also experience much higher temperatures than PWR (Pressurised water reactor) cores. In order to fully understand the requirements for enhanced fuel performance and interim/long term spent fuel storage, some efforts must be made to compare and contrast the two fuel types, to understand if LWR data are fully applicable to AGR data in various operational and storage scenarios. One such microstructural effect requiring assessment is a fuel microstructure commonly referred to as high burnup structure (HBS). The current study describes a series of post-irradiation examinations (PIE) undertaken on AGR fuel. A total of circa 30 AGR samples are examined in which HBS is present, and a further similar size of samples in which no HBS was present. Observations include SEM (scanning electron microscopy) and LOM (light optical microscopy) providing a characterisation of the appearance of HBS in AGR. The results are supported by burnup profile modelling, and assessment of fuel temperature from metallographic markers. The results are consistent with AGR outer ring fuel exhibiting an onset of HBS at a rod average burnup of ∼30 MWd/kgU and a 100 μm HBS thickness at a rod average burnup of 40 MWd/kgU. These values are lower than the comparable (pellet average) burnup for PWR fuel. The difference in burnup is shown to be due to the neutron spectrum in AGR fuel elements, and which also leads to a marked variation in HBS thickness around the circumference of AGR fuel. There is no suggestion that the local onset burnup for HBS formation differs between the two fuel types.